Criteria for eligibility to cisplatin in the curative treatment of head and neck cancer: Consensus opinion from a panel of experts. (November 2018) - de Castro, Gilberto; Alves, Gustavo V.; Castro, Ana F.; Chaves, Aline L.F.; De Marchi, Pedro; de Oliveira, Thiago B.; Dias, Fernando L.; Guindalini, Rodrigo S.C.; Nicolau, Ulisses R.; Soares, Andrey; Mora, Paulo A.R.
Abstract: Squamous-cell carcinoma of the head and neck (SCCHN) is an important problem in Brazil, where epidemiological and socioeconomic features often create barriers to the implementation of combined modalities with curative potential. Cisplatin improves the efficacy of radiotherapy in the adjuvant treatment of localized SCCHN and in the definitive therapy of locally advanced disease. However, the addition of high-dose cisplatin to radiotherapy increases treatment toxicity and is not always warranted. A panel of experts convened in Sao Paulo, Brazil, for discussions and recommendations regarding the use of high-dose cisplatin in combination with radiotherapy in SCCHN. In addition to discussing their professional experience, panel members used the current literature to provide evidence-based, practical recommendations regarding sociodemographic or medical criteria that may preclude safe administration of cisplatin. It is hoped that the application of these recommendations in clinical practice may improve therapeutic results in Brazil and other countries with similar health-care environments.